Current Advances in Coptidis Rhizoma for Gastrointestinal and Other Cancers - Zhong, Zhangfeng (Frontiers in Pharmacology, 2022)
Cancer is a serious disease with an increasing number of reported cases and high mortality worldwide. Gastrointestinal cancer defines a group of cancers in the digestive system, e.g., liver cancer, colorectal cancer, and gastric cancer. Coptidis Rhizoma (C. Rhizoma; Huanglian, in Chinese) is a classical Chinese medicinal botanical drug for the treatment of gastrointestinal disorders and has been shown to have a wide variety of pharmacological activity, including antifungal, antivirus, anticancer, antidiabetic, hypoglycemic, and cardioprotective effects. Recent studies on C. Rhizoma present significant progress on its anticancer effects and the corresponding mechanisms as well as its clinical applications. Herein, keywords related to C. Rhizoma, cancer, gastrointestinal cancer, and omics were searched in PubMed and the Web of Science databases, and more than three hundred recent publications were reviewed and discussed. C. Rhizoma extract along with its main components, berberine, palmatine, coptisine, magnoflorine, jatrorrhizine, epiberberine, oxyepiberberine, oxyberberine, dihydroberberine, columbamine, limonin, and derivatives, are reviewed. We describe novel and classic anticancer mechanisms from various perspectives of pharmacology, pharmaceutical chemistry, and pharmaceutics. Researchers have transformed the chemical structures and drug delivery systems of these components to obtain better efficacy and bioavailability of C. Rhizoma. Furthermore, C. Rhizoma in combination with other drugs and their clinical application are also summarized. Take together, C. Rhizoma has broad prospects as a potential adjuvant candidate against cancers, making it reasonable to conduct additional preclinical studies and clinical trials in gastrointestinal cancer in the future.